Global Economic Prospects : Commodity Markets Outlook, October 2014 - Baffes, John (World Bank Group, Washington, DC, 2014)
Commodity prices are expected to remain weak for the remainder of 2014 and, perhaps through much of 2015. Crude oil has seen one of the sharpest declines, down more than 20 percent to $83/barrel (bbl) on October 15 from this year’s high of $108/bbl in mid-June. Agricultural prices have weakened as well, down 6 percent since June. Metal prices remained relatively stable, from the sharp declines seen in 2011. A slowdown in the Euro area and emerging economies, a strong US dollar, increased oil supplies, and good crop prospects for most agricultural commodities have contributed to the recent gyrations in markets.